The varied facets of history : essays in honour of Aniruddha Ray - Ray, Aniruddha; Alam, Ishrat; Hussain, Syed Ejaz. (Delhi : Primus Books, 2011)
Festschrift for Aniruddha Ray, former professor, Dept. of Islamic History and Culture, University of Calcutta; contributed articles.
Includes bibliographical references (p. [281]-289) and index.
Keywords: History in literature; India -- History -- 1000-1765.; Bengal (India) -- History